Guards of the peach orchard. - Lev Grigorevich Brodaty:::Creator::::::::::::
Glava Dvadtsat Shestaya' (Chapter 26). The guards at the entrance of the peach orchard at which Joads work as scabs. Pen and ink lithograph. Lev Grigorevich Brodaty was born in Warsaw in 1889. A graphic artist, poster artist and illustrator, he created these for a Russian translation (possibly the first) of The Grapes of Wrath. He died in Moscow in 1954.